Technical Guidelines for Small Island Mapping with UAVs - World Bank (World Bank, Washington, DC, 2020)
Image acquisition and surveying using unmanned aerial vehicles (UAVs) is a very promising technology for Small Island Developing States (SIDS). UAVs can be a relatively low-cost data collection tool at the surveying scales often needed in small island contexts. Further, UAVs can capture thousands of images in a single flight and provide greater detail than satellites or even manned aircraft. The World Bank and Humanitarian OpenStreetMap Team (HOT) compiled this guidance note to document experience and best practices in the use and operation of UAVs for economic development in SIDS. Many of the lessons presented in this guidance note stem from the UAV4Resilience organized by the World Bank (World Bank 2017b) and from experiences with Pacific Drone Imagery Dashboard (PacDID) deployments in the Pacific islands (HOT 2016). This report is intended for local technological agencies of island nations that work to operationalize UAVs as a standard data collection tool.